Drive angry - Lussier, Patrick; Cage, Nicolas, 1965-; Heard, Amber, 1986-; Fichtner, William (Universal City, CA : Summit Entertainment, 2011)
An undead criminal escapes from hell to avenge his daughter's murder and rescue her kidnapped baby from a cult.
Originally released as a motion picture in 2011.
Features: Access: "Drive angry," audio commentary with filmmakers Patrick Lussier & Todd Farmer.
Nicolas Cage, Amber Heard, William Fichtner, Billy Burke, David Morse.
MPAA rating: R.
Blu-ray disc, DTS-HD Master Audio 5.1.
This is a Blu-ray disc which can only be played on Blu-ray disc players and will not play on standard DVD players.
Keywords: Demonology -- Drama; Revenge -- Drama; Hell -- Drama; Video recordings for the hearing impaired; Fiction films; Thriller films; Feature films; Action and adventure films; Fantasy films